Gene-environment interactions and the enteric nervous system: Neural plasticity and Hirschsprung disease prevention - Heuckeroth, Robert O.; Schäfer, Karl Herbert (Developmental biology, 2016)
Intestinal function is primarily controlled by an intrinsic nervous system of the bowel called the enteric nervous system (ENS). The cells of the ENS are neural crest derivatives that migrate into and through the bowel during early stages of organogenesis before differentiating into a wide variety of neurons and glia. Although genetic factors critically underlie ENS development, it is now clear that many non-genetic factors may influence the number of enteric neurons, types of enteric neurons, and ratio of neurons to glia. These non-genetic influences include dietary nutrients and medicines that may impact ENS structure and function before or after birth. This review summarizes current data about gene-environment interactions that affect ENS development and suggests that these factors may contribute to human intestinal motility disorders like Hirschsprung disease or irritable bowel syndrome.